Emergency Surgical Management of Upper Airway Obstruction: Perioperative Nursing Roles - Deecharoen, Supavadee; Klaewklong, Natnarun (Siriraj Medical Bulletin, 2025)
The upper respiratory tract comprises the nasal cavities, paranasal sinuses, oral cavity, pharynx, and larynx. Any dysfunction, anatomical abnormality, or pathological lesion within these structures can lead to partial or complete upper airway obstruction. This condition can occur suddenly (acute) or develop progressively (chronic) and poses a significant threat to the patient’s ability to ventilate and oxygenate adequately. Common clinical manifestations include dyspnea, respiratory distress, stridor, restlessness, cyanosis, and in severe cases, loss of consciousness. Without immediate medical intervention, upper airway obstruction can rapidly progress to respiratory failure and death. Emergency tracheostomy is considered a definitive and life-saving surgical procedure in managing critical airway obstructions, especially when endotracheal intubation is not feasible. Perioperative nurses play a pivotal role in the management of patients requiring emergency tracheostomy. Their responsibilities extend beyond routine surgical preparation to include rapid assessment of airway compromise, early recognition of signs and symptoms, and effective communication with the multidisciplinary team. Furthermore, perioperative nurses are responsible for ensuring the availability and functionality of specialized surgical instruments and airway management equipment under urgent conditions. Their preparedness directly influences the efficiency of surgical intervention and patient outcomes. This article highlights the essential perioperative nursing roles in emergency airway management, emphasizing the importance of clinical competency, critical thinking, and teamwork. Timely, coordinated nursing care significantly contributes to reducing complications, improving patient safety, and enhancing survival rates in patients with upper airway obstruction.